Respostas

2013-08-30T17:11:18-03:00
3x + 2√81     -      72
   3        3 - 5x = 4x + 1
3x + 2 =        √9          
    3        3 -1 = 4x + 5x
3x + 2 =     3    
    3        2 = 9x
3x + 2 =     3   
    3        2 - 9x
(2 - 9x)(3x + 2) = 3.3
(6x + 4 - 27x² - 18x) = 9
27x² - 12x + 4 - 9 = 0
27x² - 12x - 5 = 0

Δ = (-12)² - 4.27.(-5)
Δ = 144 + 540
Δ = 680

x = -(-12) +/- √680
          2.27
x = 12 +/- 2
√10
           54

x' = 12 + 2
√10 :2
            54
x' = 6 + 
√10
          27

x'' = 12 - 2
√10 :2
           54
x'' = 6 - 
√10
          27